2001
DOI: 10.1108/09534810110394895
|View full text |Cite
|
Sign up to set email alerts
|

Dramatism as method: the promise of praxis

Abstract: “Praxis” is the stated goal of Radical Humanist scholarship. But, this has been a goal without realization, and without method. To our knowledge there is no record of the realization of this goal in a management context. This paper reports our effort to develop a method to achieve praxis – “dramatism” as suggested by the work of Kenneth Burke, our “field test” of dramatism in a business setting, and the extent of our “success.” Our partial success points to refinements in the method, as it applies to Critical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…70–2). Studies in organizations purporting to derive their method from Burke – however indirectly – have been undertaken (Case, 2001; Graham‐Hill and Grimes 2001; Kendall, 1993; Mangham and Overington, 1983; Pine and Gilmore, 1999; Walker and Monin, 2001). [1] As Geertz (1983 p. 27) remarked some 20 years ago, Burke's influence is ‘at once enormous and – because almost no one actually uses his baroque vocabulary, with its reductions, ratios and so on – elusive’.…”
Section: Literature Reviewmentioning
confidence: 99%
“…70–2). Studies in organizations purporting to derive their method from Burke – however indirectly – have been undertaken (Case, 2001; Graham‐Hill and Grimes 2001; Kendall, 1993; Mangham and Overington, 1983; Pine and Gilmore, 1999; Walker and Monin, 2001). [1] As Geertz (1983 p. 27) remarked some 20 years ago, Burke's influence is ‘at once enormous and – because almost no one actually uses his baroque vocabulary, with its reductions, ratios and so on – elusive’.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Especially in the past two decades, there have been many studies conducted to measure the efficiency of training with drama by scientists dealing with the business management field (Baron, Harris et.al, 2001;Beckwith, 2003;Corsun, Young, McManus, & Erdem, 2006;Cunha, Kamoche, & Cunda, 1999;Fisk & Grove, 1996;Gardner & Avolio, 1998;Gibb, 2004;Goddard, 1999;Goodwin, 1996;Grahan-Hill & Grimes, 2001;Harris & Spiro, 1981;Harvey, 2001;Higgs, 1993;Higgs, 1993;Hsu, 1989;Häpfl & Schreyägg, 2004;Mayer, 2001;Moshavi, 2001;O'Neill & Lambert, 1982;Pearce, 2006;Pearce & Jackson,2006;Vera, 2004;Williams & Anderson, 2005) When the literature is reviewed, it is observed that mostly the "Creative Drama" -with its more common name "Role Playing"-type is used as the subject of many studies in the business management literature in the early periods when drama technique was first used.…”
Section: The Effects Of Drama Training On Organizations and Managersmentioning
confidence: 99%
“…Marketing (Fisk & Grove, 1996;Goodwin, 1996) and Organisational Management (Gardner, 1992;Graham-Hill & Grimes, 2001;Harvey, 2001;Oswick et al, 2001;Walker & Monin, 2001;Wood, 2002). Following the examples of Goffman (1959) and Burns (1972), who each use the concepts and terminology in theatre to make the 'unfamiliar social world' accessible to others, I saw potential for using this metaphor here, to provide a consistent means of describing behaviour across the different samples and sites proposed.…”
Section: Theatre As An Adjunct To Ethnographymentioning
confidence: 99%